Making and Unmaking Airports in Tunu (East Greenland): The Socio-Material Dynamics of Hope and Connectivity - Elixhauser, Sophie (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
Like many airports throughout the Arctic, Kulusuk Airport, the entrance to the sparsely populated East Coast of Greenland, is built on the remnants of past military activities and is located some distance from the regional capital, Tasiilaq. For years, there have been discussions regarding the construction of a new airport in Tasiilaq to improve connectivity and reduce dependence on helicopter flights. Throughout the East Coast, many residents feel that they are looked down upon by the (West) Greenlandic population and are given little priority in the political and economic decisions taking place in the faraway national capital of Nuuk, which feeds into residents’ attitudes towards the ever-suspended airport plans. Many residents place great hope on this plan, as this “infrastructural hope” (Reeves 2017) includes economic and social possibilities and an improvement of the region’s status both within the country and abroad. On the other hand, in the village of Kulusuk, near the current airport, people fear the repercussions of this new airport. I explore the hopes, fears, and affect generated by and embedded within infrastructure, considering issues of remoteness, social and physical connectivity, “infrastructural violence” (Rodgers and O’Neill 2012), and residents’ future imaginaries and historical experiences in (post)colonial Greenland. Describing the socio-material dynamics of hope and connectivity, this article shows how aviation infrastructure is never just about the physical infrastructure but is always enabled by and embedded in societal processes.